An evaluation of the reanalyses ERA-Interim and ERA5 in the Arctic using N-ICE2015 data - Fredriksen, Liv-Ellen (UiT The Arctic University of Norway, 2018)
The Arctic climate has changed considerably in the last few decades. Hence, a large fraction of the current studies of the Arctic climate relies on global atmospheric reanalyses, due to the shortage of meteorological observations in the Arctic. However, global climate models have shown to struggle with simulating the current conditions in the Arctic region. Thus, the objective of this thesis is to evaluate how accurate the reanalysis ERA-Interim and ERA5 are in representing the measurements from the Norwegian Young Sea Ice (N-ICE2015) expedition obtained in 2015 North for Svalbard. The observations from N-ICE2015 are a good data set for using in the evaluation. The reason for this is due to the fact that N-ICE2015 provide measurements obtained over the thinner sea ice condition in the Arctic during the winter season, which no other Arctic expedition can provide. Moreover, the ERA5 reanalysis is newest reanalysis produced and few studies have evaluated on ERA5’s performance in the Arctic. In addition, the thesis will focus on how the assimilated N-ICE2015 observations affect the reanalyses ERA-Interim and ERA5. Final objective is to see if new reanalysis ERA5 shows improvements relative to ERA-Interim representing the previous reanalysis generation.